KEBIJAKAN PENGEMBANGAN DESTINASI PARIWISATA CIANJUR SELATAN DI KABUPATEN CIANJUR JAWA BARAT - Yaya Mulyana; Abu Huraerah; Rudi Martiawan (JISPO : Jurnal Ilmu Sosial dan Ilmu Politik, 2019)
Tourism has grown spectacularly as a mainstay sector of various countries in gaining foreign exchange and economic growth, including Indonesia. Likewise for one of the regions in Indonesia, namely Cianjur Regency which has a variety of interesting tourist attractions and is visited by tourists such as Cipanas. Tourism in Cianjur Regency is not only North Cianjur but also in South Cianjur has very potential tourism potential. But unfortunately, the management is not optimal so that its potential has not been explored. Therefore, this study will examine the extent of Cianjur Regency tourism policy in developing South Cianjur tourism. This study uses descriptive analysis method to explore the object under study. The type of data used is data in the form of interviews and secondary results. The results of the study show that the policies that have been implemented have not been able to improve the performance of the tourism sector optimally. Some indicators that have not been optimal include infrastructure development, tourism promotion, and commitment to policy implementation.